Analisis Sistem Informasi Arsip Keuangan pada PT Pertamina Unit Pemasaran I - Sabila Devia Miralda (Jurnal Pustaka Nusantara dan Budaya, 2013)
The purpose of this research was to analyze the information system of the financial archives on PT Pertamina Marketing Unit I. in this case, we would like to know the problems in managing the archives and to give the recommendation to develop the information system of automatic archives. The methods in this research were using descriptive research and qualitative approaching. The determination of the informant was done by purposive sampling method. Data was collected by using observation on archival unit of work and deep interview to executive employees of archives. Analyzing the data was done by grouping the data from the result of the interview and observation based on examination of assumption to the problems and the pattern the answers from the interview. The result of this research indicated that the process mechanism of implementation of archival information system was not working properly due to some reasons. It appeared because the archival information system was done manually using Microsoft Excel to entry the data. Rhere were some problems in using manual system that cause the inefficiently in searching-back the archives. Due to huge amount of the archives, it would be better if managing the archives supported by the computer-based system. The research has identified various obstacles in managing the archives manually and given the input to improve the archival information system. Increasing the insight and the knowledge about archival information system and reviewing the possibility to complete the task with the support of information technology. We expect the system capable to process the archives dynamically which is active and in-active, also having the features that easy to understand and manageable. Based on the result  of the need of the system, the one that fit appropriately to fulfill the need is Dynamical Archival Information System.